TOTAL JOINT ARTHROPLASTY IN YOUNG PATIENTS: INDICATIONS, RISKS, AND LONG-TERM OUTCOMES - Kacper Zima,; Agnieszka Kiedik,; Zuzanna Pietruk,; Jakub Chamier-Gliszczyński,; Julia Kozłowska ,; Sylwia Skraińska,; Przemysław Siemiątkowski,; Dominik Ryszard Płaza, (International Journal of Innovative Technologies in Social Science, 2026)
Total joint arthroplasty (TJA) of the hip and knee is one of the most successful reconstructive procedures in modern orthopedics, providing significant pain relief and functional improvement. Over the past decades, a steady increase in the number of arthroplasty procedures performed in younger patients, commonly defined as individuals under 60 years of age, has been observed worldwide. This demographic shift poses unique clinical challenges, as younger patients present higher functional demands, longer life expectancy, and a substantially increased risk of revision surgery compared with elderly populations. The aim of this narrative review is to summarize current evidence regarding indications for total hip and knee arthroplasty in young patients, analyze perioperative and long-term risks, and discuss implant survivorship and functional outcomes. Furthermore, emerging technologies and treatment strategies designed to prolong implant longevity and delay revision surgery are reviewed. A comprehensive understanding of these factors is essential for appropriate patient selection, surgical planning, and long-term management of young individuals undergoing joint replacement.